Enhancing Economic Incentives For Accelerated Agricultural Development - Agipar, Bakyei; Makhatovich, Bolatkhan Makhatov; Dagys, Kadirbyek; Ablayeva, Elmira; Yergeshovich, Bazarkhan Rustembaev (Mongolian Journal of Agricultural Sciences, 2024)
Economic incentives play a vital role in fostering the development of key economic sectors, particularly in enhancing the competitiveness and growth of the agricultural sector. The aim of this study is to evaluate the state policy on economic incentives supporting agricultural development in both macro- and microeconomic contexts and to propose recommendations for further improvement of state support, incentives, and levers of influence. Since this research falls into a policy study, it employs widely used policy analysis methods. The findings, including assessments, conclusions, and recommendations, as well as the calculations and justifications presented, aim to inform agricultural policymakers, decision-makers, and food and agriculture specialists at all levels. The study’s novelty lies in its analysis of the theoretical and methodological foundations of state participation and economic levers in the agricultural sector, interpreted Mongolia's specific context. Additionally, it develops principles, methodology, and criteria for assessing the need for economic support and stimulation, offering a rationale for calculations to enhance economic incentives.